The Influence of Taste and Packaging on Purchasing Decisions with the Intervening Variable Purchase Interest - Aminatuzzahro’, Siti; Nurhayati , Nurhayati; Firdaus, Firdaus (Economics and Business International Conference Proceeding, 2024)
The purpose of this research is to determine the effect of taste and packaging on purchasing decisions with variables that intervene in buying interest. The population in this study is consumers who buy in Lapak Pasar Durian which is infinite. Sampling technique using purposive sampling technique. The sample in this study used 96 respondents. This research method uses quantitative and analytical methods used in this research is SmartPLS 3 software. The results of research show that Cita Rasa has an influence on Buying Interest. Packaging has an influence on buying interest. Taste has an influence on the Purchase Decision. Packaging has no influence on the Purchase Decision. Buying interest has an influence on the Purchase Decision. The results of this research have several implications for sellers in Lapak Pasar Durian. First, the taste of durian that is good and in accordance with the tastes of consumers is very important to increase interest and purchase decisions. Second, attractive and functional packaging can increase consumer buying interest. Third, packaging is not always the main factor in purchasing decisions. Lastly, efforts to increase consumer buying interest will have a positive impact on purchasing decisions.